Abundance of Xanthium spinosum L. along the different land types and its impacts on invaded plant communities in North Shewa Zone, Ethiopia - Amare Assefa; Gebiyaw Tilaye (Sustinere: Journal of Environment and Sustainability, 2023)
A biological invasion is a form of biological pollution that is most likely more terrible than chemical pollution. Xanthium spinosum is one of the most invasive alien plant species. However, its abundance and impacts on invaded plant communities have not yet thoroughly studied. This study aimed to investigate the abundance and impacts of X. spinosum on invaded plant communities in the North Shewa Zone, Ethiopia. The study applied the quadrat method, sampling 80 main plots within 1 m2. Differences in mean cover-abundances of X. spinosum across various land types were compared using one-way-ANOVA followed by Tukey’s Honestly Significant Difference (HSD) Test. The results showed that roadsides and flooded areas exhibited the maximum mean cover-abundance of X. spinosum compared to farmland and rangeland. The number of plant species recorded was 106 in the control areas, compared to only 73 in the invaded areas. Hence, the number of plant species decreased by 31.13% in the infested area compared to the control. Thus, X. spinosum was among the factors contributing to the reduction of plant diversity, affecting the sustainability of biodiversity in the study areas.  Therefore, implementing management measures against the spread of X. spinosum is to address the ongoing threat to biodiversity.